The physical Features of South Sudan - Okic Yor, Dr. Angelo (IJRDO Journal of History & Geography, 2021)
The study wanted to discuss the background of South Sudan. It also aimed to describe the location of South Sudan, climate, soil, and natural vegetation. In the same time, the paper concentrate on population of South Sudan, their economic activities. Nevertheless, the study would like to discuss the physical features of South Sudan, official language use in the country. In addition, the study aimed to determine the states of South Sudan. Also, determine the national parks in South Sudan. The study used primary and secondary source to obtain data collection. Also, the qualitative and quantitative descriptive methods was employed for a finding of the physical features of South Sudan. On the same way, the study recommended to the researchers to focus on availing complete information about South Sudan as new nation to the entire global population.